IMPROVING THE ABILITY OF WRITING A NARRATIVE CHARGE BY USING ANIMATED IMAGES MEDIA STUDENT CLASS V.B SD NEGERI 17 LUBUKLINGGAU - Noermanzah Noermanzah; Syaiful Abid; Septaria Septaria (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2018)
The objective of this research was to explain the improvement of writing captions narrative using animated media images of class V.B SD Negeri 17 Lubuklinggau. The research method used was classroom action research. This research was conducted in two cycles. Techniques of collecting data using test and observation techniques. The research process of each cycle was done through four stages: planning, implementation, observation, and reflection. The subjects of this study are students of class V.B with a total of 29 students consisting of 18 male students and 11 female students. The results showed that there was an increase in the ability to write a narrative essay of class V.B SD Negeri 17 Lubuklinggau by using animation media images. This is evidenced by students who get the value of â‰¥ 70 or who have completed in cycle two reached 93.10%. From the results of this study the Indonesian language teachers can use the animated media images in improving the ability to write narrative essay and ability on other basic competencies. Keywords: writing skills, narrative essay, animated picture media